Strengthening Character Through Character Habitus in Students of the Sociology Education Study Program and Pancasila and Citizenship Education - Suardi Suardi; Muhajir Muhajir (JED (Jurnal Etika Demokrasi), 2022)
The problem of this research is that students experience demoralization of character so that they need character strengthening in the lecture process at college. The purpose of the research is to shape the character of students through character habitus in the lecture process. This study uses the mix-method concurrent embedded method with 10 research informants and 55 research respondents. The research data was collected using questionnaires, interviews, documentation and observations, then the data were analyzed using qualitative and quantitative data analysis. The results showed that character strengthening through character habitus in three levels, namely habitus dissemination by lecturers, acceptance of habitus by students and collective habitus by lecturers and students through the lecture process. Habitus character provides reinforcement for the character of discipline, responsibility, religious, honest, hard work, independent, curiosity, respect for achievement and a love of reading for students of the Sociology Education study program and students of the Pancasila and Citizenship Education Study Program, University of Muhammadiyah Makassar.Masalah penelitian ini adalah mahasiswa mengalami demoralisasi karakter sehingga membutuhkan penguatan karakter dalam proses perkuliahan di perguruan tinggi. Tujuan penelitian adalah untuk membentuk karakter mahasiswa melalui habitus karakter dalam proses perkuliahan. Penelitian ini menggunakan metode mix-method concurrent embedded dengan informan penelitian 10 orang dan responden penelitian 55 orang. Pengumpulan data penelitian menggunakan angket, wawancara, dokumentasi dan observasi, kemudian data dianalisis menggunakan analisis data kualitatif dan kuantitatif. Hasil penelitian menunjukkan penguatan karakter melalui habitus karakter dalam tiga tingkatan yaitu desiminasi habitus yang dilakukan dosen, penerimaan habitus oleh mahasiswa dan habitus kolektif oleh dosen dan mahasiswa melalui proses perkuliahan. Habitus karakter memberikan penguatan pada karakter disiplin, tanggung jawab, religious, jujur, kerja keras, mandiri, rasa ingin tahu, menghargai prestasi dan gemar membaca pada mahasiswa program studi Pendidikan Sosiologi dan mahasiswa Program Studi Pendidikan Pancasila dan Kewarganegaraan Universitas Muhammadiyah Makassar.